O problema do livre-arbítrio: O argumento incompatibilista de Peter Van Inwagen em An Essay on Free Will - Fachin, Patricia Ribolli (Universidade do Vale do Rio dos Sinos, 2019)
This thesis aims to present Peter van Inwagen's work on the problem of free will, as expressed in An Essay on Free Will (1983). Such approach does not investigate what free will is in itself or whether agents have free will, but rather examines whether free will and determinism may be compatible. Hence, this work is divided into three chapters. The first one addresses the problem of free will from the resolution of the problem of compatibilism, as well as the deterministic and free-will theses. The second chapter exposes van Inwagen's analysis of three compatibilist arguments followed by his objections. Finally, the last chapter presents van Inwagen's incompatibilist argument, the Argument of Consequence, and some reasons why the philosopher argues that it is preferable one to commit to free will rather than to the thesis of determinism.
Keywords: Livre-arbítrio; Determinismo; Compatibilismo; Incompatibilismo; Peter van Inwagen; Free will; Determinism; Compatibilism; Incompatibilism; Peter van; Inwagen; ACCNPQ::Ciências Humanas::Filosofia